Biology Laboratory: Facilities, Infrastructure and Utilization in Biology Learning - Ghina Risnawati Aliyah; Etika Dyah Puspitasari (Journal on Biology and Instruction, 2022)
Permendiknas No 24 of the 2007 rule are a requirement to support practicum activities. This study aims to determine the suitability of laboratory infrastructure, types of biology laboratory utilization, and the constraints that affect biology practicum activities. This research is a literature study using 30 articles. Search for articles using online databases with search keywords for articles "the use of laboratory biology", "biological laboratories", "biological laboratory facilities and infrastructure", "utilization of biological laboratories", and "biological practicum analysis" and the time range between 2010-2020. The data analysis technique of this research uses descriptive analysis techniques. The results showed that most of the biology laboratory facilities and infrastructure in schools accordance with Permendiknas standards No. 24 of 2007. Types of the utilization of the biology laboratory include carrying out practicum activities, functioning to increase student learning outcomes, and utilizing practicum tools and materials. Obstacles that affect biology practicum activities are space design that is not appropriate with the rules, practicum schedule is not yet available, practicum tools and materials are limited, laboratory staff is not available, budget constraints are limited, and obstacles coming from teachers